Data communications and networks - Miller, Dave (McGraw-Hill, 2006)
A friendlier voice in an area crowded with technical, formal textbooks, Miller’s style reaches the students quickly and effectively. The abundance of chapter projects and the audio/visual support of concepts enables instructors to keep students engaged.